Freezing of Gait in Parkinson’s Disease Is Associated with Reduced 6-[18F]Fluoro-L-m-tyrosine Uptake in the Locus Coeruleus - Sayaka Asari Ono; Toshihiko Sato; Shin-ichi Muramatsu (Parkinson's Disease)
Freezing of gait (FOG) is a common disorder in Parkinson’s disease (PD) and could be attributed to a reduction in brain noradrenaline. The aim of this study was to determine the relationship between aromatic L-amino acid decarboxylase (AADC) activity in the locus coeruleus (LC) and FOG in PD using high-resolution positron emission tomography with an AADC tracer, 6-[18F]fluoro-L-m-tyrosine (FMT). We assessed 40 patients with PD and 11 age-matched healthy individuals. PD was diagnosed based on the UK Brain Bank criteria by two movement disorder experts. FOG was directly observed by the clinician and assessed using a patient questionnaire. FMT uptake in the LC, caudate, and putamen was analyzed using PMOD software on coregistered magnetic resonance images. FOG was present in 30 patients. The severity of FOG correlated with the decrease of FMT uptake in the LC regardless of disease duration and the severity of other motor impairments, indicating dysfunction of the noradrenergic network in FOG.